The study of unit trust company in educating Malaysian people towards unit trust: a case study of Permodalan Nasional Berhad (PNB) / Mohd Faiz Zakaria - Zakaria, Mohd Faiz (Faculty of Business and Management, 2009)
This chapter present the overall picture of the company background, its subsidiary company and unit trust product that owned by Permodalan Nasional Berhad (PNB). It also present all about the unit trust background in the Malaysian market.